Determinants of debt structure in ACE Market Bursa Malaysia: a panel data analysis - Ghasemi, Maziar (Academic Research Publishing Group, 2018)
This study was conducted with the aim to examine the relevance of different financing theories namely Agency Theory, Trade-Off Theory and Pecking Order Theory to explain capital structure choices among firms in "Access, Certainty, Efficiency" (ACE) Market of Bursa Malaysia. The ACE Market is the financing source for the high-growth and technology requirements of middle-sized firms. The literature on debt policy decision making in the ACE market have been scant, leading the scholars to realize the necessity of performing more studies in this field. To further explain this issue, this study performed a quantitative analysis on a panel data sample of 60 ACE firms from 2005 to 2016. Three proxies for leverage namely total, long-term and short-term debts were examined based on the total assets and equity in six regression models. From seven variables examined in this study, findings indicated a significant relationship between warrant and debt in all models. In addition, liquidity, firm size, profitability and leverage showed significant relationship in all the models except for long-term debt. However, reputation, non-debt tax shield and interest tax shield were seen significant in some models. Trade-off Theory and Pecking Order Theory can jointly clarify determinants of firms’ capital structure in the ACE Market.